Endogenous HCN Channels Modulate the Firing Activity of Globus Pallidus Neurons in Parkinsonian Animals - Hao, Xiao-Meng; Xu, Rong; Chen, An-Qi; Sun, Feng-Jiao; Wang, Ying; Liu, Hong-Xia; Chen, Hua; Xue, Yan; Chen, Lei (Frontiers in Aging Neuroscience, 2019)
The globus pallidus occupies a critical position in the indirect pathway of the basal ganglia motor control system. Hyperpolarization-activated cyclic-nucleotide gated (HCN) channels play an important role in the modulation of neuronal excitability. In vivo extracellular single unit recording, behavioral test and immunohistochemistry were performed to explore the possible modulation of endogenous HCN channels in the globus pallidus under parkinsonian states. In MPTP parkinsonian mice, micro-pressure application of the selective HCN channel antagonist, ZD7288, decreased the firing rate in 10 out of the 28 pallidal neurons, while increased the firing rate in another 15 out of the 28 neurons. In 6-OHDA parkinsonian rats, ZD7288 also bidirectionally regulated the spontaneous firing activity of the globus pallidus neurons. The proportion of pallidal neurons with ZD7288-induced slowing of firing rate tended to reduce in both parkinsonian animals. Morphological studies revealed a weaker staining of HCN channels in the globus pallidus under parkinsonian state. Finally, behavioral study demonstrated that intrapallidal microinjection of ZD7288 alleviated locomotor deficits in MPTP parkinsonian mice. These results suggest that endogenous HCN channels modulate the activities of pallidal neurons under parkinsonian states.